Chemoselective hydrogenation of cinnamaldehyde over Pd/CeO2-ZrO2 catalysts - Bhogeswararao, Seemala; Srinivas, D. (Catalysis Letters, 2010)
Selective hydrogenation of cinnamaldehyde over Pd (2 wt%) supported on CeO2, ZrO2 and CeO2-ZrO2 catalysts is reported for the first time. In general, the olefinic (C=C) group of cinnamaldehyde is preferentially hydrogenated compared to the carbonyl (C=O) group. This selectivity preference could, however, be altered or reversed by adding alkali additives to the catalyst. The influence of additive on the structure and redox properties of the active sites and correlation of that with selective hydrogenation activity is investigated.
Keywords: alpha; beta-Unsaturated aldehyde; Ceria-zirconia; Cinnamaldehyde; Hydrogenation; palladium catalyst

Intramolecular selective hydrogenation of cinnamaldehyde over CeO2-ZrO2-supported Pt catalysts - Bhogeswararao, Seemala; Srinivas, D. (Journal of Catalysis, 2012)
Selective liquid phase hydrogenation of cinnamaldehyde is reported, for the first time, over CeO2, ZrO2, and CeO2-ZrO2-supported Pt catalysts. Cinnamyl alcohol is the selective product. These catalysts are highly active and selective even at 25 degrees C and found to be superior to most of the hitherto known supported Pt catalysts. Alkali addition (NaOH) has enhanced the performance of these catalysts. At an optimized reaction condition, 95.8% conversion of cinnamaldehyde and 93.4% selectivity of cinnamyl alcohol have been obtained. Acidity of the support (due to the presence of ZrO2 component) and higher electron density at Pt (due to CeO2 component) are attributed to be responsible for the superior catalytic activity of Pt supported on CeO2-ZrO2 composite material. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: alpha; beta-Unsaturated aldehyde; Ceria-zirconia; Cinnamaldehyde; Hydrogenation; Promotion by alkali ions; Supported Pt catalyst

Catalytic activity of ZIF-8 in the synthesis of styrene carbonate from CO2 and styrene oxide - Zhu, Minqi; Srinivas, Darbha; Bhogeswararao, Seemala; Ratnasamy, Paul; Carreon, Moises A. (Catalysis Communications, 2013)
The catalytic activity of ZIF-8 in the synthesis of styrene carbonate from carbon dioxide and styrene oxide is presented. ZIF-8 crystals displayed catalytic activity even at temperatures as low as 50 degrees C, with styrene carbonate yields as high as similar to 54% at 100 degrees C. In contrast to many prior-art catalysts, solvents or co-catalysts were not required. Pyridine and ammonia were used as probe molecules to estimate the type and density of acid sites in fresh and reused ZIF-8 catalysts. DRIFT spectroscopy of adsorbed pyridine revealed the presence of both Bronsted (B) and Lewis (L) acid sites. The B-sites have nearly vanished in the case of recycled ZIF-8 catalysts. The simultaneous presence of both the acid sites and the nitrogen basic moieties from the imidazole linker in ZIF-8 promoted the adsorption of the CO2 on the solid surface and its further conversion to the cyclic carbonate. The ZIF-8 catalysts could be recycled and reused without significant loss in catalytic activity. Published by Elsevier B.V.
Keywords: CO2 conversion; cyclic carbonates; Styrene carbonate; Zeolitic imidazolate frameworks; ZIF-8

Noble metal promoted CeO2-ZrO2-supported ni catalysts for liquid-phase hydrogenation of cinnamaldehyde - Bhogeswararao, Seemala; Kumar, V. Pavan; Chary, K. V. R.; Srinivas, D. (Catalysis Letters, 2013)
Pd or Pt promoted CeO2-ZrO2-supported Ni catalysts exhibited superior catalytic activity to the hitherto known Ni catalysts for liquid-phase hydrogenation of cinnamaldehyde at moderate conditions. Under similar experimental conditions, the unpromoted catalyst was selective for hydrocinnamaldehyde product (C=C hydrogenation) whereas the promoted catalyst yielded 3-phenyl propanol (C=C and C=O hydrogenation product). Enhanced dispersion of Ni was the cause for higher activity of the promoted Ni catalysts.
Keywords: Ceria-zirconia; Cinnamaldehyde; Noble metal promoted catalyst; Selective hydrogenation; Supported Ni catalyst

Catalytic conversion of furfural to industrial chemicals over supported Pt and Pd catalysts - Bhogeswararao, Seemala; Srinivas, D. (Journal of Catalysis, 2015)
Several industrial chemicals were prepared by hydrogenation of furfural over gamma-Al2O3-supported Pt and Pd catalysts. These catalysts were active even at room temperature (25 degrees C). While the Pt catalysts were selective for C=O hydrogenation (yielding furfuryl alcohol), Pd facilitated ring hydrogenation (producing tetrahydrofurfuryl alcohol). At high temperature (240 degrees C), the Pd catalyst exhibited excellent decarbonylation activity forming furan with 85% yield. The catalyst was reusable even in the absence of external hydrogen. The presence of hydrogen led to ring-opened products. Furan was quantitatively converted at 25 degrees C to tetrahydrofuran. Acidity of the support made a marked influence on the activity and selectivity. Pt on SO4-ZrO2 favored hydrogenolysis yielding 2-methyl furan along with furan with >75 wt% selectivity. Particle size, metal dispersion, and solvent influenced catalytic activity. Differences in structure and mode of furfural adsorption were also the causes for variations in selectivity of these supported Pt and Pd catalysts. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Biomass to fuels and chemicals; Decarbonylation; furfural; Hydrogenation; Hydrogenolysis; Supported Pt and Pd catalysts